Public-Sector Innovation To Narrow The Urban–Rural Digital Divide For Inclusive Smart Tourism In Indonesia: A Systematic Review - Rina Herawati, Augustin; Widi Lestari, Asih; Hayu Dwimawanti, Ida (Iapa Proceedings Conference, 2025)
This systematic review synthesizes evidence on government-led digital innovations advancing inclusive smart tourism in Indonesia and narrowing the urban–rural digital divide. We examine smart-tourism apps, QR-based cashless payments, destination management systems, chatbots, and AR/VR, alongside public programs for broadband expansion, youth skills, and smart villages. Findings indicate these measures improve access for Gen Z/Millennial travelers and rural SMEs, enable data-driven management, and broaden market reach. Persistent gaps in connectivity, digital literacy, and local capacity limit impact. We outline implications for digital inclusion, regional equity, and youth-focused growth and propose priorities for sustainable policy design.